Seven new species of the leafhopper genus Salka Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae) from China - Song, Yue-Hua; Li, Zi-Zhong (Zootaxa, 2012)
In the present paper, seven new species, Salka cerviprocessa, S. congjianga, S. fanjinga, S. guilinensis, S. songae, S. taoyuanensis and S. triprocessa spp. n. from China are described and illustrated.